An intrinsic physical content of “single photon power” − (hν∙Δν) - Salkov, E.A.; Svechnikov, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Considered in this paper is the possibility to use information properties of photon noise inherent to thermal radiation. Using the calculations of threshold limitations for detecting the fluctuations of thermal radiation as a signal and not disturbances only, we have adduced some arguments concerning the phenomenological content of the “power of a single photon” qΔν ≡ hν∙Δν not defined earlier, where the frequency band Δν is determined by an observation spectral slit. It has been shown that a non-traditional view of “photonic noise” determined by this factor appears in relation with the fluctuations of the photon flux at the observation spectral slit. With definite measurement parameters, this kind of noise is capable to append some essential points to classical models of photon noises and even block access to measurements of fluctuations in the power of thermal radiation. Also adduced are supplementary considerations concerning the existing models of arising shot noise at the photo detector output as a result of physical-and-statistical specificity of the electron excitation process and its kinetics. Offered is a model for a background radiator, which allows us performing the numerical calculations with the use of the specific parameters of the background structure.